Sexual Harassment in the Name of Religion and Heaven as Shown in Walid’s Film: Symbolic and Feminist Critical Approach - Syamsurrijal, Syamsurrijal; Iswadi, Muhamad Khalid; Arniati, Fitri (LPPM Universitas Bumigora Mataram, 2025)
This paper examines the phenomenon of sexual harassment cloaked in religious legitimacy through an analysis of the film Walid (2025), a cinematic work that critiques the abuse of religious authority. The background of cases of sexual violence in Lombok, especially in Islamic boarding schools and educational institutions, shows the existence of unequal power relations and a culture of silence that worsens the situation of victims. Walid’s film depicts charismatic religious leaders who manipulate sacred teachings to establish absolute power and commit symbolic and sexual violence. The main objectives of this study are to: (a) identify the forms of sexual harassment that are justified in the name of religion, (b) analyze the representation of religious power in films as social criticism, and (c) provide social reflections to encourage the reform of the protection system in the religious environment. This research employs a descriptive qualitative method, analyzing the theories of Power and Symbolic Relations (Michel Foucault), Symbolic Violence (Pierre Bourdieu), and Feminist Critical Theology. The findings of the study show that Walid is not only a fictional representation, but also a reflective means that expose the oppressive power structures in religious institutions, as well as invite the public to build critical awareness, fight for justice for victims, and reject all forms of violence that take refuge behind religious symbols.